656 DIFFERENTIAL DIAGNOSIS BETWEEN TAKOTSUBO SYNDROME AND MYOCARDITIS. (15th December 2022) - Biddau, Mattia; Garau, Enrica; Marchetti, Maria Francesca; Utzeri, Elena; Licciardi, Marco; Mandas, Martina; Maiani, Silvia; Cau, Riccardo; Saba, Luca; Montisci, Roberta
Abstract: Background: In the evaluation of specific non MINOCA, the differential diagnosis between Takotsubo syndrome and myocarditis can be challenging. Purpose: The aim of our study was to evaluate the parameters that can be more useful to distinguish the pathologies. Methods: All the patients with specific non MINOCA admitted to our service were enrolled. Informations about clinical characteristic, in-hospital outcome and complications were collected. All the patients have made several blood samples for hS-troponin, CRP, NT-proBNP, ECG with calculation of QTc, cardiac echocardiogram at the admission and at the discharge and diagnosis has always been confirmed by CMR. Results: Between October 2018 and October 2021 51 specific non MINOCA have been hospitalized in our service (26 Takotsubo and 25 myocarditis). Patients affected by Takotsubo syndrome were more frequent older, females (p<0, 0001), had a higher global cardiovascular risk (p=0, 046) and had more frequently neurological disorders (p=0, 041), autoimmune thyroiditis (p=0, 02) and have experienced stressful triggers before hospital admission (p=0, 003); patients with myocarditis had, instead, more often an infection before hospital admission (p<0, 0001). No differences have been found in clinical or electrocardiographic presentation, although observing the evolution of the ECG, a significative prolongation of the QTc in Takotsubo have been noticed (QTc 552 ± 75, 1 vs 409, 8 ± 27, 7 p<0, 0001). Peak troponins, NT-proBNP and CRP were significantly different (p=0, 002; p=0, 008; p=0, 003), as were LVEF and WMSI at the admission (p=0, 004 and p<0, 0001). From the CMR data LGE and T2 mapping were useful to distinguish the two pathologies (p<0, 0001; p=0, 001). From the analysis of ROC curves a T2 mapping value superior to 62 msec was able to distinguish the two pathologies with a sensibility of 70%, a specificity of 73%, a positive predictive value of 73% and a negative predictive value of 70%. Conclusion: There are many parameters useful to distinguish the specific non MINOCA: clinical characteristics; blood sample parameters like troponins, CRP and NT-proBNP; ECG, echocardiographic and CRM. T2 mapping can distinguish the two pathologies with a good sensibility and specificity.